Study guides

☆☆

Q: 3a plus 2b - 6 - 2a - b plus 4?

Write your answer...

Submit

Still have questions?

Related questions

2a + 3a + 4 = 5a + 4

a = 3a + 4 0 = 2a + 4 2a = -4 a = -2

sample problem 9b + 3a - a + 6+ 2b + 4 terms would be each number or number plus a variable separated by an operation symbol (+ or -) like terms would be 9b and 2b, 3a and -a, and 6 and 4 simply add 9b + 2b (which is 11b) 3a-a (which is 2a) and 6 + 4 (which is 10) your answer would then be 11b + 2a + 10 hope that helped

a + b - 2 is the answer in simplest terms. without telling us what a or b is this is the most accurate answer.

(5a+8) - (2a+4) =3a +4 To do this, simply subtract like terms. 5a-2a=3a and 8-4=4

Do this: write it out 2 |2a + 4b + 8 Now what divides into all the numbers? ---------------- a + 2b + 4 answer is 2(a+2b+4)

It can be simplified to: 3a^2 +10a+7 or factored as (3a+7)(a+1)

(2a - 1)(3a + 4)

2a2

3+2*A+B*4/2-4 = 3 + 2A + 2B - 4 = 2A + 2B - 1

3a + 2b is an expression in algebra. If you make 3a + 2b equal to something then you can find the values of "a" and "b" Lets say you make 3a + 2b equal to 23 3a + 2b = 23 Now find "a" and "b" to make this equation true... 3(5) + 2(4) = 23 15 + 8 = 23 23 = 23 Correct So in this case a=5 and b=4

3a=3xa and if a = 5 it would be 3x5 which = 15 2b=2xb and if b = 2 it would be 2x2 which = 4 15+4=19

When simplified it is: 2a+8b+4

(2a - 3)(3a - 4)

It is: (2a+3)(3a+4) when factored

7

3a + 2b = 4If b = 7, then3a + 2(7) = 43a + 14 = 4Subtract 14 from each side:3a = -10Divide each side by 3:a = -10/3

The idea here is to combine terms that have the same variable (or, in more complicated cases, the same combination of variables). For example, 3a + 2a is the same as 5a.

-2

5a - 5 = 7 + 2a ( subtract 2a from both sides) 3a - 5 = 7 (add 5 to both sides) 3a = 12 ( divide both sides by 3) a = 4

(3a+4)/12 - (5/3) = (2a-1)/2Multiply each side by 12:(3a+4) - (20) = 6 (2a-1)Eliminate the parentheses:3a + 4 - 20 = 12a -63a -16 = 12a -6Add 6 to each side:3a -10 = 12aSubtract 3a from each side:-10 = 9aDivide each side by 9:-10/9 = a

I think you have 2a + 3b = 13 2b = 8 If so, the second equation gives, by dividing both sides by 2, b = 4 then plug in b = 4 in first equation 2a + 3(4) = 13 2a + 12 = 13 2a = 1 a = 1/2

It is 6a + 4

4(2a+b) + 2(6a+2b) Working this out it is: 8a + 4b + 12a + 4b = 20a + 8b or 4(5a+2b).

4y - 4 + 3a + 7 - 6a - 4 = 4y -1 - 3a